RUNX3 as a Potential Predictor of Metastasis in Human Pancreatic Cancer - ROSSI, ERNESTO (In Vivo, 2017)
Background/Aim: In genetically engineered murine models of pancreatic ductal adenocarcinomas (PDAC), high levels of Runx3 increase the metastatic potential of cancer cells. Ιn this study we evaluated the role of Runx3 in human pancreatic cancer. Materials and Methods: Runx3 was retrospectively assessed by immunohistochemistry in seventy-eight tumor samples of patients who underwent surgical resection for PDCA and were followed at least for 24 months. Results: Thirty-two cases resulted completely negative for Runx3; forty-six showed highly variable expression. We established an optimal cut-off value of Runx3 in predicting distant metastasis equal to 0.04. The odds ratio (ORs) for development of distant metastases at multivariate analysis for patients having Runx3 ≥0.04 was 4.26 (p=0.043) and 4.68 (p=0.032) after adjusting for residual tumor and treatment, respectively; OR for development of metastases in multiple sites was 4.28 (p=0.025) for Runx3 ≥0.04. Conclusion: Our results support the ability of Runx3 to contribute to the dissemination of human PDAC thus confirming the observations from murine models.